Production and purification of xylitol by Scheffersomyces amazonenses via sugarcane hemicellulosic hydrolysate - Silva, Débora D.V. [UNESP]; Dussán, Kelly J. [UNESP]; Idarraga, Angela; Grangeiro, Luana [UNESP]; Silva, Silvio S.; Cardona, Carlos A.; Quintero, Julián; Felipe, Maria G.A. (Wiley, 2020)
Xylitol was produced by Scheffersomyces amazonensis UFMG-HMD-26.3 in hemicellulosic hydrolysate obtained from a mixture of sugarcane bagasse and straw (1:1) in batch fermentation, and was recovered using supercritical fluid. The xylitol produced was 20.11 g L−1 and the extraction approach reached a xylitol recovery of 40.51% at a high purity level of 99.59%. An analysis of energy consumption for the xylitol production process showed that xylitol production from sugarcane biomass hemicellulosic hydrolysate is feasible, highlighting the potential use of this biomass in sustainable xylitol production and supercritical fluids as a robust proposal for xylitol separation. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.
Keywords: energy consumption; Scheffersomyces amazonensis; sugarcane biomass; supercritical CO2; xylitol recovery